Predicting global potential distribution of Peromyscopsylla hesperomys and Orchopeas sexdentatus and risk assessment for invading China under climate change - Li, Hongyun; Liang, Ying; Dong, Li; Li, Cancan; Zhang, Lu; Wang, Bin; Ma, Delong; Mu, Qunzheng; Wang, Jun; Hou, Haifeng; Liu, Qiyong (Frontiers in Public Health, 2023)
Abstract: Background: Peromyscopsylla hesperomys and Orchopeas sexdentatus are regarded to be representative plague vectors in the United States. Plague is making a comeback and its incidence is rising globally, possibly due to climate change and environmental damage. Environmental factors such as temperature and precipitation have a significant impact on the temporal and spatial distribution of plague vectors. Methods: Maximum entropy models (MaxEnt) were utilized to predict the distributions of these two fleas and their trends into the future. The main environmental factors influencing the distribution of these two fleas were analyzed. A risk assessment system was constructed to calculate the invasion risk values of the species. Results: Temperature has a significant effect on the distribution of the potential suitable areas for P. hesperomys and O. sexdentatus. They have the potential to survive in suitable areas of China in the future. The risk assessment system indicated that the risk level for the invasion of these two species into China was moderate. Conclusion: In order to achieve early detection, early interception and early management, China should perfect its monitoring infrastructure and develop scientific prevention and control strategies to prevent the invasion of foreign flea vector.